Labelling of food products : good marketing versus legal obligation - Štefanić, Ivan (Array, 2018)
Declaring nutritional characteristics, expiration dates and instructions for safe preparation of food, substances causing potential allergies or intolerances contained in products may be of vital importance to buyers and consumers. Additional information, such as geographical indication or origin of the food and compliance with certain standards could play a decisive role in purchasing decisions. A comprehensive search of regulatory framework of food production, processing, distribution and labelling is conducted at the Croatian and EU level. Appropriate emphasis is given to the food-related legislation, marketing and intellectual property related legislation. Special attention is given to the declaration of: nutritional characteristics, substances or products causing allergies or intolerances; geographical indication and origin of the food; quality seals; medicinal claims, organic food claims, and redundant, confusing and misleading signs. Legal obligations regarding mandatory food labelling are limited in terms of information. Voluntary food labelling can offer a large array of additional information, but it is still regulated in a very precise manner. Marketing communication, regarding their own brands, is an important component of the business for several reasons; it is an effective signpost for repeated purchases; an entry barrier into the sector or possible sources of additional revenue. Manufacturers and traders can voluntarily apply labelling standards that are more stringent than minimally prescribed ones. In this way, they communicate their concern for customers’ well-being and possibly achieve a competitive advantage over producers who do not demonstrate such a degree of social responsibility in their business.